Cytoprotective effects of molsidomine against methotrexate-induced hepatotoxicity: an experimental rat study - Samdanci, Emine Turkmen; Huz, Mustafa; Ozhan, Onural; Tanbek, Kevser; Pamukcu, Esra; Akatli, Ayse Nur; Parlakpinar, Hakan (Dove Medical Press Ltd, 2019)
Introduction and aim: Methotrexate (Mtx) is an antineoplastic and immunosuppressive drug that may cause hepatotoxicity, whereas molsidomine (Mol) is a vasodilating and antioxidant agent. This study aimed to investigate the potential protective effects of Mol in Mtx-induced liver toxicity in rats. Materials and methods: Forty Wistar albino rats were equally divided into five groups: control, Mol, Mtx, Mol Mtx, and Mtx Mol. Following treatment, the animals were sacrificed, and liver tissue samples were histopathologically evaluated using Roening grading and Bcl-2 antibody staining. Tissue oxidants, antioxidants, and serum transaminases were measured and statistically compared across all groups. Results: No hepatic fibrosis or steatosis was observed in any of the groups. In the Mtx group, grade 2 liver injury and score 2 Bcl-2 antibody staining were observed; however, in the Mol-Mtx group, these were lower (grade 1, score 1). There were no statistically significant differences in serum transaminase levels among groups. Malondialdehyde levels were higher in all rats that received Mtx, but no differences in myeloperoxidase levels were observed among the groups. Levels of tissue antioxidants, including superoxide dismutase, glutathione (GSH) peroxidase (GSH-Px), and reduced GSH, were significantly higher in the Mol-treated and Mol pre-treated groups. Catalan (CAT) levels were elevated in all Mol-treated groups, but only in that group were CAT levels statistically significantly higher than in the control group. Conclusion: Our results suggest that some oxidant levels could increase following Mtx administration in the liver, possibly contributing to liver damage, whereas Mol could mitigate the histopathological and biochemical effects of hepatotoxicity. However, molecular studies are required to understand the exact mechanisms of these alterations.
Keywords: methotrexate; molsidomine; hepatotoxicity; hepatic fibrosis